Detection of a Novel DSPP Mutation by NGS in a Population Isolate in Madagascar - Bloch-Zupan, Agnès; Huckert, Mathilde; Stoetzel, Corinne; Meyer, Julia; Geoffroy, Véronique; Razafindrakoto, Rabisoa W.; Ralison, Saholy N.; Randrianaivo, Jean-Claude; Ralison, Georgette; Andriamasinoro, Rija O.; Ramanampamaharana, Rija H.; Randrianazary, Solofomanantsoa E.; et al. (Frontiers in Physiology, 2016)
A large family from a small village in Madagascar, Antanetilava, is known to present with coloured teeth. Through previous collaboration and 4 successive visits in 1994, 2004, 2005 and 2012, we provided dental care to the inhabitants and diagnosed dentinogenesis imperfecta. Recently, using whole exome sequencing we confirmed the clinical diagnosis by identifying a novel single nucleotide deletion in exon 5 of DSPP. This paper underlines the necessity of long run research, the importance of international and interpersonal collaborations as well as the major contribution of next generation sequencing tools in the genetic diagnosis of rare oro-dental anomalies. This study is registered in ClinicalTrials (https://clinicaltrials.gov) under the number NCT02397824.